A Rubric Report 2023 Ṙ “The Profile of a Post Doctoral Research” (Global Journals of Research in Engineering, 2023)
Pioneering experiments with promising results and ironically lay unpublished is paradoxical But that is what had happened to him as the another years ago in 2013 Yet the continuing relevance of the ideas and similar pursuit by others prompted him now in 2023 to publish his post doctoral works as it knowledge matters and its chronology too His doctoral thesis Anna University 2008 was on Trifemur a wear tester for hip joint prostheses his patented invention Subsequently he augmented it as a versatile tribometer for the orthopaedic implants Dimpled femur ball spinal discs special coating and lubricants could get unacceleratedly test-measured for their natural wear-life span Pilot test runs on shells and discs proved successful it was ready to test dimpled femur ball as well